2007
DOI: 10.1111/j.1365-2567.2007.02691.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD4+ CD25+ regulatory T cells correlate with chronic hepatitis B infection

Abstract: Summary Circulating CD4+ CD25+ regulatory T cells (Tregs) have been demonstrated to maintain immunotolerance and suppress the antigen‐specific or antigen‐non‐specific T‐cell responses, but their role in chronic hepatitis B (CHB) infection in humans has not been well characterized. In this study, we analysed the frequency and phenotypic characteristics of CD4+ CD25+ Tregs in patients of different hepatitis B virus (HBV) infection status, and investigated the effect of Tregs on antiviral immune responses in CHB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
136
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 44 publications
12
136
2
1
Order By: Relevance
“…36,37 In our study, a large proportion of peripheral Tregs observed in the periphery of CHB patients also express high levels of PD-1, even after 48 weeks of adefovir and suppression of HBV VL, predisposing them to impaired responsiveness to antigenic stimulation or apoptosis soon after activation. 26,27 Additionally, we were able to demonstrate diminished but still high levels of FoxP3 While other studies have examined the role of a PD-1 blockade in regulating Tregs for hepatitis C virus infection, our study demonstrated the effectiveness of PD-1 blockade in HIV/HBV-infected patients. 38 Since many effector T cells and Tregs in CHB patients express PD-1, it is unclear whether the enhancement of HBV-specific immunity observed in our patients is due to a direct effect on T cells, T effector memory cells, or both.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…36,37 In our study, a large proportion of peripheral Tregs observed in the periphery of CHB patients also express high levels of PD-1, even after 48 weeks of adefovir and suppression of HBV VL, predisposing them to impaired responsiveness to antigenic stimulation or apoptosis soon after activation. 26,27 Additionally, we were able to demonstrate diminished but still high levels of FoxP3 While other studies have examined the role of a PD-1 blockade in regulating Tregs for hepatitis C virus infection, our study demonstrated the effectiveness of PD-1 blockade in HIV/HBV-infected patients. 38 Since many effector T cells and Tregs in CHB patients express PD-1, it is unclear whether the enhancement of HBV-specific immunity observed in our patients is due to a direct effect on T cells, T effector memory cells, or both.…”
Section: Discussionmentioning
confidence: 62%
“…[25][26][27] Treg expansion has also been demonstrated in HIV viremic patients, 13 but the relationship between HBV replication and Treg expansion has not been studied in detail in HIV/HBV-coinfected patients. In addition, to our knowledge, no studies have examined a functional role for Tregs in CHB patients before and after control of HBV replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, impaired immune response contributes to the failure of viral clearance. Immunosuppressive CD4 + Foxp3 + T regs have been associated with the progression and prognosis of HBV infection by previous studies [7][8][9]. Studies have demonstrated the negative role of T regs in immune response to HBV infection, including suppression of HBV-specific Th cells, suppression of proliferation of virus-specific CD8 + T cells [10][11][12], and reduction of IFN-g production [7].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, during the research on chronic HBV infection, it was found that the frequency of CD4+CD25+ Tregs significantly increased in peripheral blood of CHB patients totally when compared with healthy controls, and had a positive correlation with serum HBV DNA load in CHB patients, with >10 7 copies/ml serum HBV DNA. Furthermore, the depletion of CD4+CD25+Tregs leads to the increase of HBV Ag-stimulated IFN-γ production and cellular proliferation of peripheral blood mononuclear cells (PBMCs) from HBV-infected patients, and co-culture of CD4+CD25+Tregs with effector cells significantly suppressed HBV Ag-stimulated IFN-γ production and cellular proliferation (8,9). Thus, although the exact mechanism has not been well defined yet, Tregs may play an important role in HBV persistence by modulating virus-specific immune responses.…”
Section: Introductionmentioning
confidence: 99%